Evidence for direct-acting oxidative genotoxicity by reduction products of azo dyes. - Sweeney, E A (1994)
The intestinal flora forms a complex ecosystem that metabolizes dietary and endogenous nutrients under primarily anaerobic conditions. The ingestion of azo dyes has been proposed as one source of potential genotoxic agents. Many intestinal bacteria are able to reduce the azo bond (termed azofission), which liberates the substituted naphthol compounds. The standard Ames test has not demonstrated mutagenicity either by various common food colorings or by their reduced end products in Salmonella typhimurium strains TA98 and TA100. In contrast, genetic toxicity was demonstrated in the Escherichia coli differential kill assay and in S. typhimurium TA102 for the reduced dyes. The superoxide free radical was produced by the azo dyes only after reduction by the intestinal bacteria Enterococcus faecalis and Bacteroides thetaiotaomicron.